Learning Materials Utilizing Sustainability Pedagogy in Grade 8 Ecology - Esmeth Espinola (SEAMEO QITEP in Science, 2024)
Science education in the Philippines is anchored on the United Nations (UN) goals on sustainability education, as provided in K to 12 Science Curriculum, which envisions learners to be environmentally literate, critical problem solvers, and responsible stewards of nature. However, K to 12 implementations in the Philippines faced several challenges that resulted in student’s poor awareness and knowledge about Philippine wildlife and conservation, as well as low proficiency in science. In order to enhance the proficiency and competence of students in ecology, learning materials utilising sustainability pedagogy were developed. A Descriptive-developmental research method was used to evaluate the developed learning materials (DLMs) and describe the experiences of students in the DLMs. A Four-Point Likert Scale technique was employed to evaluate the DLMs. structured journaling and thematic analysis were used to determine the experiences of students in using the DLMs in ecology. The experts’ evaluation showed that the five DLMs utilising sustainability pedagogy in grade 8 ecology passed the criteria of DepEd (Department of Education) as stipulated in the Learning Resources Management and Development System (LRMDS). Introduced features, sustainability-themed, issue-based, contextualised, and reflective likewise obtained very satisfactory result. Students found the DLMs interesting, comprehensible, promote awareness, relevant to the community’s environmental issues, and helped them to express their opinions. The study recommended that the valid and modified DLMs utilising sustainability pedagogy may be used by biology teachers in their lessons, can still be improved and further contextualised as well as used in other topics in ecology and environmental science.